Influence of alternating magnetic field on non-newtonian blood perfusion and transport of nanoparticles in tissues with embedded blood vessel during hyperthermia - Sreedhara Rao Gunakala; Victor M. Job; P.V.S.N. Murthy; Sateesh Sakhamuri (Ain Shams Engineering Journal, 2023)
In this paper, we consider the impact of an alternating magnetic field on axisymmetric non-Newtonian nanofluid flow and nanoparticle (magnetite or iron-platinum) transport through a blood vessel and surrounding tissue during hyperthermia therapy. The geometrical domain of the problem is divided into four regions; the blood vessel region, cancerous and non-cancerous muscle or prostate regions, and a fat region. Each of the tissue regions is considered to be a saturated porous material that admits fluid flow, which is given by the Darcy-Brinkman-Forchheimer model. The Quemada model is used to describe the non-Newtonian nature of blood in each region. The resulting unsteady coupled governing equations and corresponding boundary and initial conditions are numerically solved by using the finite element method with Taylor-Hood elements. A physically realistic range of parameter values are used when numerically solving the governing equations. Using the obtained numerical solution, the effects of magnetic field amplitude and oscillation frequency, inlet nanoparticle solid volume fraction and nanoparticle diameter on nanofluid velocity, temperature, pressure and nanoparticle distribution are examined. The results determined that more heat generation is achieved with a larger volume fraction of injected nanoparticles and higher magnetic field amplitude. Also, heat generation is maximized by using nanoparticles with a diameter near 15nm and a magnetic field oscillation frequency near 4×104s-1. Thus, the present study provides an improved understanding of the factors influencing the effectiveness of intravenous magnetic hyperthermia cancer therapy in muscle and prostate tissues. The heat generated by the considered nanoparticles under an alternating magnetic field can be more accurately predicted and controlled using the two-phase non-Newtonian model of fluid flow and convective heat and mass transfer that is investigated herein.